Factors associated with small-for-gestational-age births among preterm babies born - Grace J Chan; Amha Mekasha; Ahmed Ali; Mesfin K Debere; Damen Haile Mariam (BMJ Open, 2022)
Objectives This study aimed to determine the prevalence of small-for-gestational-age (SGA) and appropriate-for-gestational-age (AGA); compare variations in multiple risk factors, and identify factors associated with SGA births among preterm babies born <2000 g.Design Cross-sectional study.Setting The study was conducted at five public hospitals in Oromia Regional State and Addis Ababa City Administration, Ethiopia.Participants 531 singleton preterm babies born <2000 g from March 2017 to February 2019.Outcome measures Birth size-for-gestational-age was an outcome variable. Birth size-for-gestational-age centiles were produced using Intergrowth-21st data. Newborn birth size-for-gestational-age below the 10th percentile were classified as SGA; those>10th to 90th percentiles were classified as AGA; those >90th percentiles, as large-for-gestational-age, according to sex. SGA and AGA prevalence were determined. Babies were compared for variations in multiple risk factors.Results Among 531 babies included, the sex distribution was: 55.44% males and 44.56% females. The prevalences of SGA and AGA were 46.14% and 53.86%, respectively. The percentage of SGA was slightly greater among males (47.62%) than females (44.30%), but not statistically significant The prevalence of SGA was significantly varied between pre-eclamptic mothers (32.42%, 95% CI 22.36% to 43.22%) and non-pre-eclamptic mothers (57.94%, 95% CI 53.21% to 62.54%). Mothers who had a history of stillbirth (adjusted OR (AOR) 2.96 95% CI 1.04 to 8.54), pre-eclamptic mothers (AOR 3.36, 95% CI 1.95 to 5.79) and being born extremely low birth weight (AOR 10.48, 95% CI 2.24 to 49.02) were risk factors significantly associated with SGA in this population.Conclusion Prevalence of SGA was very high in these population in the study area. Maternal pre-eclampsia substantially increases the risk of SGA. Hence, given the negative consequences of SGA, maternal and newborn health frameworks must look for and use evidence on gestational age and birth weight to assess the newborn’s risks and direct care.